The control of soil-transmitted helminthiases in the Philippines: the story continues - Mary Lorraine S. Mationg; Veronica L. Tallo; Gail M. Williams; Catherine A. Gordon; Archie C. A. Clements; Donald P. McManus; Darren J. Gray (BMC, 2021)
Abstract Background Soil-transmitted helminth (STH) infections have long been an important public health concern in the Philippines. In this review, we describe the current status of STH infections there and highlight the control efforts undertaken to reduce STH burden. Main text A nationwide STH mass drug administration (MDA) programme was started in 2006 but the overall STH prevalence remains stubbornly high across the Philippines, ranging from 24.9% to 97.4%. The continued increase in the prevalence may have been due to the challenges related to MDA implementation which include the lack of people's awareness about the importance of regular treatment, misconceptions about the MDA strategy, lack of confidence on the drugs used, fear of adverse events and general distrust of government programs. There are existing water, sanitation and hygiene (WASH) programmes implemented in communities [e.g., Community-Led Total Sanitation (CLTS) program and providing toilet bowls and provision of subsidy for latrine construction] and schools [e.g., WASH in School (WINS) program], but sustained implementation is required to achieve expected outcomes. Although WASH in general is being taught in schools, integration of STH as a disease and community problem in the current public elementary school curriculum is still inadequate. The Integrated Helminth Control Program (IHCP) currently implemented in the country, which is focused on improved sanitation and personal hygiene, health education and preventive chemotherapy, will require continuous appraisal. The sustainability of this programme still continues to be a challenge. Conclusions Despite the major efforts to control STH infections for almost two decades in the Philippines, persistently high STH prevalence has been reported across the country, which is likely due to suboptimal MDA coverage and limitations in WASH and health education programs. Sustainable delivery of integrated control approaches will continue to play a pivotal role in the control and elimination of STH in the Philippines. Graphic abstract